2013
DOI: 10.1016/j.ympev.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked cryptic endemism in copepods: Systematics and natural history of the calanoid subgenus Occidodiaptomus Borutzky 1991 (Copepoda, Calanoida, Diaptomidae)

Abstract: a b s t r a c tOur comprehension of the phylogeny and diversity of most inland-water crustaceans is currently hampered by their pronounced morphological bradytely, which contributed to the affirmation of the ''Cosmopolitanism Paradigm'' of freshwater taxa. However, growing evidence of the existence of cryptic diversity and molecular regionalism is available for calanoid copepods, thus stressing the need for careful morphological and molecular studies in order to soundly investigate the systematics, diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 66 publications
1
87
0
1
Order By: Relevance
“…They have been found in a wide range of crustacean taxa including calanoid copepods (Bucklin et al, 1999(Bucklin et al, , 2000Machida and Lin, 2017) and diaptomid calanoids (Thum and Harrison, 2009;Marrone et al, 2013). The aberrant sequences found in this study do not contain any stop codons or frame shifts, and therefore do not resemble classical nuclear mitochondrial pseudogenes (so called numts) that often contain InDels (Insertion/Deletions) and mutations at any codon position (Song et al, 2008;Buhay, 2009;Calvignac et al, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…They have been found in a wide range of crustacean taxa including calanoid copepods (Bucklin et al, 1999(Bucklin et al, , 2000Machida and Lin, 2017) and diaptomid calanoids (Thum and Harrison, 2009;Marrone et al, 2013). The aberrant sequences found in this study do not contain any stop codons or frame shifts, and therefore do not resemble classical nuclear mitochondrial pseudogenes (so called numts) that often contain InDels (Insertion/Deletions) and mutations at any codon position (Song et al, 2008;Buhay, 2009;Calvignac et al, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…Afterwards, with the advent and spreading of molecular techniques, an ever increasing amount of evidences showed that as a rule, in clear antithesis with the ''Cosmopolitan paradigm'', inland water organisms belong to a high number of different species, and that these are characterized by a noteworthy degree of endemism (e.g. Korn et al, 2006;Belyaeva & Taylor, 2009;Bode et al, 2010;Komárek & Mareš, 2012;Krienitz & Bock, 2012;Marrone et al, 2013, and references therein). The taxa belonging to these species complex are sometimes hard or impossible to be told apart based on morphology (e.g.…”
Section: Genetic Evidences About Dispersal and Colonizationmentioning
confidence: 99%
“…At a within-species level, quite a low ongoing gene flow between conspecific populations is usually observed (Boileau et al, 1992), which contributes to the presence of marked phylogeographic structures in the vast majority of inland water taxa (e.g. Gómez et al, 2000;De Gelas & De Meester, 2005;Muñoz et al, 2008;Marrone et al, 2013). Actual genetic connectivity seems to be, as a rule, scarce to absent even among nearby conspecific populations (De Meester, 1996;Meglécz & Thiéry, 2005, Ketmaier et al, 2003, but see also Aguilar, 2011), or it is not possible to single out a coherent geographic pattern in the distribution of the genetic lineages (e.g.…”
Section: Genetic Evidences About Dispersal and Colonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mega5 (Tamura, Peterson, Peterson, Stecher, Nei, & Kumar, 2011) was used to translate in amino acids the sequences of the proteincoding gene COI in order to check for the possible presence of frameshifts or premature stop codons, which would indicate the presence of sequencing errors or pseudogenes, which is a wellknown and wide-spread problem in invertebrates (e.g. Marrone, Lo Brutto, Hundsdoerfer, & Arculeo, 2013).…”
Section: Downloaded By [Universita DI Palermo] [Federico Marrone] Atmentioning
confidence: 99%